Dynamics of magnetic and electric parameters transformation in thin films of sodium-doped lanthanum manganites - Pan'kiv, L.I.; Tsmots, V.M.; Pan'kiv, I.S.; Matviyenko, A.I.; Tovstolytkin, A.I. (Functional Materials, 2012)
Transformation dynamics of magnetic and electric parameters in thin films of sodium-doped lanthanum manganite has been studied. The peculiar feature of the films is wide temperature range of the coexistence of ferromagnetic and paramagnetic phases. It has been found that the anomalies on temperature dependences of magnetization, electric resistance and magnetoresistance are shifted relative to each other contrary to the case of doped manganite single crystals, in which such anomalies are observed at almost the same temperature. Based on the magnetic measurements data and theoretical calculations, the dependence of ferromagnetic phase volume fraction Vfm on the temperature has been calculated. Vfm values have been calculated whereby maximums on temperature dependences of electric resistance and magnetoresistance have been observed. Conclusions have been formulated concerning the shape of ferromagnetic nuclei in the films under consideration.